IMPLIMENTASI MODEL(ASSURE) UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR PKn SISWA KELAS IV SD NEGERI 3 BUDI LESTARI KECAMATAN TANJUNG BINTANG TAHUN AJARAN 2015/2016 - Ponidi, Ponidi; Puastuti, Dwi; Kristina, Marilin (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
Based on the finding research, the implementation of ASSURE teaching model improves the active learning and achievement in civics of the student of class IV OF SD Negeri 3 Tanjung Bintang Element School. The increase of Students’ active learning can be seen from pre- research. It show that 50% Students are activite. In cycle 1, there are 67% students who are active. It increaces to 80% in cycle 2. The civics achievements of the students of class IV OF SD Negeri 3 Budi Lestari Tanjung Bintang Elementary School in the academik years of 2015/2016 is increased. The increase of students achievement can be seen in the pre research from teaching evaluation. It shows that the achievement of 12% of 25 students is increased. The increase in cycle 1 is 44& while 88% is in cycle 2.